1999
DOI: 10.1002/(sici)1099-0690(199904)1999:4<855::aid-ejoc855>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Common Radical Cation Intermediates in Cage Hydrocarbon Activations

Abstract: The oxidation of 3,6‐dehydrohomoadamantane (1) was achieved under chemical (NO+BF4–/EtOAc, NO+OAc–/Ac2O, and NO+BF4–/CH3CN), photochemical (photoexcited 1,2,4,5‐tetracyanobenzene), and electrochemical (Pt anode, CH3CN, NH4BF4) conditions. Supporting ab initio [density functional theory (BLYP) and Møller–Plesset perturbation theory (MP2)] computations utilizing standard basis sets, 6–31G* (optimizations) and 6–311+G* (single‐point energy evaluations), agree with the experimental results implicating the involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 63 publications
(9 reference statements)
0
26
0
Order By: Relevance
“…Our recent computational and experimental studies on the halogenation mechanisms of adamantane demonstrated that the 3°CϪH regiospecificities can only be understood in terms of the adamantane moiety being largely radical cationic in the transition structures {the adamantane radical cation (C 3v ) displays a half-broken 3°C ϪH bond}. [33] CϪH activations with weakly electrophilic oxidants (such as Hal n ϩ or Hal nϪ1 H ϩ ) are best visualized as concerted H-coupled electron transfer (HCET) involving linear [R···H···E] ϩ fragments in the transition structures for hydrogen abstraction.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent computational and experimental studies on the halogenation mechanisms of adamantane demonstrated that the 3°CϪH regiospecificities can only be understood in terms of the adamantane moiety being largely radical cationic in the transition structures {the adamantane radical cation (C 3v ) displays a half-broken 3°C ϪH bond}. [33] CϪH activations with weakly electrophilic oxidants (such as Hal n ϩ or Hal nϪ1 H ϩ ) are best visualized as concerted H-coupled electron transfer (HCET) involving linear [R···H···E] ϩ fragments in the transition structures for hydrogen abstraction.…”
Section: Introductionmentioning
confidence: 99%
“…Similar products are obtained from the pinenes. The photo-NOCAS procedure has also been carried out on the adamantane derivative 506 illustrated in Scheme 15 330 . Here again the radical cation 507 is formed and ring opening followed by trapping by the tetracyanobenzene affords the cation 508.…”
Section: Mementioning
confidence: 53%
“…. This carbocation and the JT effect on adamantane have been thoroughly investigated from a theoretical and experimental point of view 9,10,[65][66][67][68][69][70][71] . The presence of this molecular species has been inferred from the strong asymmetric broadening in the ionization band of the 7t 2 orbital from both photoelectron (PES) 18,[72][73][74] and Penning ionization (PIES) spectroscopy 18 .…”
Section: Jahn-teller Effect On the 7t 2 Orbitalmentioning
confidence: 99%